2020
DOI: 10.3390/ijms21176006
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Urease Inhibitor of Ruminal Microbiota Screened through Molecular Docking

Abstract: Inhibition of the urease activity of ruminal microbiota is not only beneficial for increasing dietary and endogenic urea-N utilization efficiency in ruminants but also might be applicable for the preservation of nitrogen fertilizer in soil and treatment of gastrointestinal and urinary tract infections caused by ureolytic bacteria. To discover urease inhibitors to efficiently target ruminal microbiota, the identified ruminal microbial metagenomic urease gene was used to construct a homology model to virtually s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The QMEAN score function is a valuable tool which provides the evaluation based on the overall quality of the homology models . The QMEAN score of the modeled TMPS2 was −0.53 closing to zero, indicating a good agreement between the modeled structure and experimental structure . The Ramachandran plot is widely applied to identify the stereochemically feasible angles of protein model, validating the skeletal conformation of a protein structure. , The plot revealed that 99.3% of the AA residues of the built TMPS2 were in allowed regions, with 86.9% residues in the most favored region, and only 0.7% in the disallowed region (Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…The QMEAN score function is a valuable tool which provides the evaluation based on the overall quality of the homology models . The QMEAN score of the modeled TMPS2 was −0.53 closing to zero, indicating a good agreement between the modeled structure and experimental structure . The Ramachandran plot is widely applied to identify the stereochemically feasible angles of protein model, validating the skeletal conformation of a protein structure. , The plot revealed that 99.3% of the AA residues of the built TMPS2 were in allowed regions, with 86.9% residues in the most favored region, and only 0.7% in the disallowed region (Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the linearized-microcystinase encoded by the linearized-microcystinase gene from bacterium YF1 may participate in degrading MC-LR ( Bourne et al, 2001 ). Purified enzymes were often used to study their functions and characteristics ( Zhang et al, 2020 ). Heterologously expressed MC-degrading proteins were very useful in investigating the biochemical pathways and subsequent MC derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…The study of ruminal microbial fermentation consisted of a control group and 3 epiberberine treatment groups, each containing 70 mL fresh rumen fluid and 140 mL anaerobic medium (Zhang et al 2020c ). Epiberberine treatment groups with the final concentration of 2, 20, and 200 μM were pre-incubated in an anaerobic chamber at 39 °C for 15 min.…”
Section: Methodsmentioning
confidence: 99%